Respiratory function in wind instrument players / Funzione respiratoria in suonatori di strumenti a fiato - Zuskin, E.; Mustajbegovic, J.; Schachter, et al., E.N. (La Medicina del Lavoro, 2009)
Background: The playing of wind instruments has been associated with changes in respiratory function. Study objectives: To investigate the effect of playing wind instruments on lung function and respiratory symptoms. Methods: The present study included 99 wind instrument players and a group of 41 string instrument players as a control from 3 major orchestras in Zagreb, Croatia. Data on chronic respiratory symptoms were recorded in all studied subjects. Lung function was measured in wind instrument players by recording maximum expiratory flow-volume curves. Results: Wind instrument players demonstrated significantly higher prevalences of sinusitis, nasal catarrh and hoarseness compared to control musicians. One wind instrument player developed asthma associated with his work. Odds ratios for wind instrument players were significant for chronic cough, chronic phlegm and chronic bronchitis by smoking habit (p